Uncovering the food heritage based on age differences - Adilah Md Ramli; Dg Khairunisa Ahmad Sapawi; Harifah Mohd Noor; Mohd Salehuddin Mohd Zahari (2020)
The study examines national food heritage awareness in Klang Valley based on age category (30-35 and >36 years old). Self-completed questionnaire survey is used on 676 respondents with the required age category and knowledgeable on food heritage. Differences are found on the association of National Food Heritage related to preservation, image, food identity and sustainable determinants (p<0.05) in adult (>36 years old). The main criteria, 'traditional value' is mostly chosen has significant differences (p<0.05). The age group's different understanding showed the view and understanding which can be used as a guide to creating an effective approachability on national food heritage.